Cullin-5 Adaptor SPSB1 Controls NF-κB Activation Downstream of Multiple Signaling Pathways - Georgana, Iliana; Maluquer de Motes, Carlos (Frontiers in Immunology, 2020)
The initiation of innate immune responses against pathogens relies on the activation of pattern-recognition receptors (PRRs) and corresponding intracellular signalling cascades. To avoid inappropriate or excessive activation of PRRs, these responses are tightly controlled. Cullin-RING E3 ubiquitin ligases (CRLs) have emerged as critical regulators of many cellular functions including innate immune activation and inflammation. CRLs form multiprotein complexes in which a Cullin protein acts as a scaffold and recruits specific adaptor proteins, which in turn recognise specific substrate proteins for ubiquitylation, hence providing selectivity. CRLs are divided into 5 main groups, each of which uses a specific group of adaptor proteins. Here, we systematically depleted all predicted substrate adaptors for the CRL5 family (the so-called SOCS-box proteins) and assessed the impact on the activation of the inflammatory transcription factor NF-κB. Depletion of SPSB1 resulted in a significant increase in NF-κB activation, indicating the importance of SPSB1 as an NF-κB negative regulator. In agreement, overexpression of SPSB1 suppressed NF-κB activity in a potent, dose-dependent manner in response to various agonists. Inhibition by SPSB1 was specific to NF-κB, because other transcription factors related to innate immunity and interferon (IFN) responses such as IRF-3, AP-1 and STATs remained unaffected by SPSB1. SPSB1 suppressed NF-κB activation induced via multiple pathways including Toll-like receptors and RNA and DNA sensing adaptors, and required the presence of its SOCS-box domain. To provide mechanistic insight, we examined phosphorylation and degradation of the inhibitor of κB (IκBα) and p65 translocation into the nucleus. Both remained unaffected by SPSB1, indicating that SPSB1 exerts its inhibitory activity downstream, or at the level, of the NF-κB heterodimer. In agreement with this, SPSB1 was found to co-precipitate with p65 after over-expression and at endogenous levels. Additionally, A549 cells stably expressing SPSB1 presented lower cytokine levels including type I IFN in response to cytokine stimulation and virus infection. Taken together, our results reveal novel regulatory mechanisms in innate immune signalling and identify the prominent role of SPSB1 in limiting NF-κB activation. Our work thus provides insights into inflammation and inflammatory diseases and new opportunities for the therapeutic targeting of NF-κB transcriptional activity.